2012
DOI: 10.1109/tmag.2012.2199967
|View full text |Cite
|
Sign up to set email alerts
|

Application and Verification of a Dynamic Vector-Hysteresis Model

Abstract: This paper presents the application and verification of a dynamic vector-hysteresis model for nonoriented ferromagnetic materials.The hysteresis model is based on the fundamental principles of thermodynamics. Since the model is completely consistent with a genuine energy interpretation it can be considered from this point of view as a mechanical analog. To validate the model, the response of the model is compared to measured material characteristics of an isotropic electrical steel grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The sum of two Langevin functions has been preferred over a single Langevin function (Steentjes et al, 2012;Rasilo et al, 2015;Steentjes et al, 2017). The addition of a second Langevin function increases the degrees of freedom, which is ideal in minimizing the fitting error after the knee region of a typical anhysteretic curve.…”
Section: Anhysteretic Magnetizationmentioning
confidence: 99%
“…The sum of two Langevin functions has been preferred over a single Langevin function (Steentjes et al, 2012;Rasilo et al, 2015;Steentjes et al, 2017). The addition of a second Langevin function increases the degrees of freedom, which is ideal in minimizing the fitting error after the knee region of a typical anhysteretic curve.…”
Section: Anhysteretic Magnetizationmentioning
confidence: 99%
“…We found that for m s = 1.23 · For numerical simulations we approximate the distribution by a mixture of N types of pseudoparticles with volume fractions ω l > 0, satisfying N l=1 ω l = 1. Each type is characterised by its own r = r l and, to account for partial reversibility of the material response [7], [12] we assign r = 0 to one of the pseudoparticle types.…”
Section: Model Of Magnetizationmentioning
confidence: 99%
“…2) we assume the magnetic field rotates, h = H m (t)(cos t, sin t), with the amplitude H m (t) = 110 min(t/6π, 1) growing with time until its maximal value 110 A/m is reached. This is a non-scalar situation and we compare the accurate numerical solution of (12), equivalent to the time discretized version of (8), to the explicit, at each time step, discretized vector play model based on the approximation (13). Although the solutions are different in the transient regime, the difference is small and disappears soon after the amplitude of the rotating magnetic field becomes constant.…”
Section: Energy Balance and Dry-friction Like Model Of Magnetizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be stressed that despite the considered approach precludes that hysteresis and eddy current effects are neglected, it may be useful as a building block for a vector hysteresis model. In some hysteresis models the thermodynamically reversible magnetisation curve, referred to as the anhysteretic, plays a crucial role [31][32][33][34][35][36]. This curve may be considered a 'spine' for the hysteresis loop; in fact it is common to assume the middle curve from the ascending and the descending loop branches as a reasonable approximation for the anhysteretic curve [31,34].…”
Section: Model Equationsmentioning
confidence: 99%